Các hệ thống tự động: bất định và điều khiển - Phàn, Vũ Ngọc (Journal of Computer Science and Cybernetics, 2016)
Model uncertainties always are hindrances to effectiveness of the control system design and  analysis. The contention of the present paper is to show that it is not capable of completely avoiding model uncertainties because the  realworld is  beyond our cognition. To find control algorithms working with model uncertainties is better than looking for the way avoiding them. The purpose of this paper is to  clarity the nature of uncertainties and control algorithms. Then, some control techniques as adaptive control, robus control, extremal control, stochastic control will be represented to demonstrate feasibilities of overcoming uncertainties.